2004
DOI: 10.1007/s00442-004-1715-z
|View full text |Cite
|
Sign up to set email alerts
|

Predation by sparrowhawks decreases with increased breeding density in a songbird, the great tit

Abstract: Predators may regulate prey populations if predation rate increases with prey density. Alternatively, if space-limited (e.g. territorial) predators become 'satiated' when prey exceed a certain density, increased prey abundance may lead to reduced predation rate. These alternatives have been difficult to test experimentally for mobile prey in the wild. We present such a test, manipulating the density of great tits (Parus major) by adding nest boxes in territories of sparrowhawks (Accipiter nisus). Predation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…As a control, we used stuffed models of the song thrush ( Turdus philomelos ) (C). Sparrowhawks are among the main predators of fledgling and adult great tits [ 25 ], while short-tailed weasels are important natural nest predators, active both during the night and during the day [ 26 ], able to enter nest boxes and representing a risk for incubating females, eggs and nestlings [ 12 , 27 ]. Song thrushes are not a threat or competitors for great tits.…”
Section: Methodsmentioning
confidence: 99%
“…As a control, we used stuffed models of the song thrush ( Turdus philomelos ) (C). Sparrowhawks are among the main predators of fledgling and adult great tits [ 25 ], while short-tailed weasels are important natural nest predators, active both during the night and during the day [ 26 ], able to enter nest boxes and representing a risk for incubating females, eggs and nestlings [ 12 , 27 ]. Song thrushes are not a threat or competitors for great tits.…”
Section: Methodsmentioning
confidence: 99%
“…The house sparrow Passer domesticus is of particular concern as it has decreased by approximately 60% over the past 40 years (Robinson et al, 2005). Previous work by Götmark and Andersson (2005) suggests that house sparrows may be at particular risk from sparrowhawk predation due to their decreasing population (Chamberlain et al, 2009), and hence we concentrate particularly on these species in this paper.…”
Section: The Motivating Garden Bird Feeding Survey Datamentioning
confidence: 99%
“…Furthermore, there are certain species, in particular House Sparrow and Starling, which are showing significant population declines in many urbanised areas of Europe. Götmark and Post (1996) found that species such as these that commonly forage on the ground were especially susceptible to Sparrowhawk attack, and negative densitydependent predation rates observed in declining species suggest that House Sparrow and Starling may be especially at risk (Götmark and Andersson 2005).…”
Section: Introductionmentioning
confidence: 99%